Sistem Informasi Usulan Perencanaan Program Jurusan Teknologi Informasi dan Komputer pada Politeknik Negeri Lhokseumawe Berbasis Web - Fauzani, Lia; Huzaeni, Huzaeni; Arhami, Muhammad (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
The Information and Computer Technology Department of Lhokseumawe State Polytechnic (PNL) does not yet have an information system for infrastructure and infrastructure needs planning, each year the laboratory chairperson, study program chairman and department secretary makes proposals for facilities and infrastructure requirements to the department head. The draft proposal is in the form of an Excel application form. The proposal made in this way made it difficult for the Head of the Department to examine proposals and revised proposals. Based on these problems an information system was proposed for the Information Technology and Computer Science Program planning program that could facilitate the department head in examining proposals and also facilitate the secretary of department, study program chairman and laboratory chairperson. in making planning proposals and revising proposals. The design of this application uses Contex Diagrams, Data Flow Diagrams and Entity Relationship Diagrams, besides that the language used in making this system is the PHP programming language and the MySQL database to store each proposed data plan. This system provides features for adding, deleting, and editing any proposed planning data consisting of mobiler data, laboratory equipment data, consumable data, activity data and learning facilities and infrastructure data. This system makes it easy for the department head to see each planning proposal data in the form of a report that can be printed which consists of the mobiler data report, lab tool data report, consumables data report, activity data report and learning data facilities and infrastructure.Keywords— Planning, Information Technology and Computers, Data Flow Diagrams, PHP, Mysql